The Influence of Green Human Resource Management on the Corporate Sustainability through Green Innovation Mediation and Corporate Social Responsibility Moderation in PDAM Surya Sembada Surabaya City - Pratama, Raditya Yuniar Alfani; Riyadi, Slamet; Sumiati, Sumiati (International Journal of Economics (IJEC), 2025)
This study examines a company involved in the processing and distribution of clean water for the public in Surabaya. Globalization and climate change are increasingly interconnected, impacting corporate sustainability. Companies must adapt to market demands while maintaining environmental responsibility. This research aims to analyze the relationship between green recruitment and selection, green training and development, green performance assessment, green reward and compensation, and corporate sustainability. The study employs SmartPLS for outer and inner model test analysis. The findings indicate that green recruitment and selection significantly affect green innovation but not corporate sustainability. Green training and development significantly influence green innovation but do not directly impact corporate sustainability. Green performance assessment also has a significant effect on green innovation but not on corporate sustainability. Meanwhile, green reward and compensation do not significantly affect green innovation but have a significant impact on corporate sustainability. Green innovation contributes to corporate sustainability. Furthermore, green recruitment and selection, green training and development, green performance assessment, and green reward and compensation significantly influence green innovation through corporate sustainability as an intervening variable. However, corporate social responsibility does not significantly moderate the relationship between green innovation and corporate sustainability. These findings highlight the need for companies to integrate green human resource practices to enhance innovation and long-term sustainability.